Exosomes in Food: Health Benefits and Clinical Relevance in Diseases. Issue 3 (4th December 2019) - Munir, Javaria; Lee, Mihye; Ryu, Seongho
ABSTRACT: Exosomes are membrane-bound organelles generally secreted by eukaryotic cells that contain mRNAs, microRNAs, and/or proteins. However, recent studies have reported the isolation of these particles from foods such as lemon, ginger, and milk. Owing to their absorption by intestinal cells and further travel via the bloodstream, exosomes can reach distant organs and affect overall health in both infants and adults. The potential role of food-derived exosomes (FDEs) in alleviating diseases, as well as in modulating the gut microbiota has been shown, but the underlying mechanism is still unknown. Moreover, exosomes may provide biocompatible vehicles for the delivery of anti-cancer drugs, such as doxorubicin. Thus, exosomes may allow medical nutritionists and clinicians to develop safe and targeted therapies for the treatment of various pathologies. The present review introduces FDEs and their contents, highlights their role in disease and infant/adult health, and explores their potential use as therapeutic agents.